THE STUDY ON EFFECTIVE USAGE OF SOCIAL MEDIA MARKETING SERVICES IN HIGHER EDUCATIONAL INSTITUTIONS (Spectrum Journal of Innovation, Reforms and Development, 2024)
This study explores the effective usage of social media marketing services in higher educational institutions. The research investigates how various social media platforms can be leveraged to enhance student recruitment, engagement, and retention. Through a comprehensive analysis of current practices, the study identifies key strategies and tools that institutions can employ to maximize their online presence and connect with prospective and current students. The findings highlight the importance of tailored content, consistent interaction, and the integration of data analytics to monitor and improve marketing efforts. Additionally, the study examines the challenges faced by institutions in implementing social media marketing and offers practical recommendations for overcoming these obstacles.